Sinergi Peran Kepala Sekolah sebagai Pemimpin Spiritual dan Akademik - Ika Kartika; Siti Maryam; Wildya Agna Rihma; Chaerunnisa; Nia Trisnawati; Titono Wahyudi (Ikatan Dai Indonesia, 2025)
School leadership encompasses various aspects, including the role as both a spiritual and academic leader. However, in practice, many school principals have yet to optimally fulfill these two roles in a balanced manner. Principals tend to focus more on technical and administrative matters, while their role in fostering a spiritual culture within the school is often overlooked. As a result, there is an imbalance between students' academic achievements and character development at school. Therefore, the purpose of this study is to examine the concept of school leadership, particularly the dual role as a spiritual and academic leader, to explore how these roles are synergized within the school environment, and to identify the challenges faced in realizing balanced and effective leadership. The findings indicate that the implementation of spiritual and academic leadership in schools is inseparable from various internal and external challenges, such as the lack of principals' understanding regarding these roles and limited support from the school community. Nevertheless, several strategies can be applied to address these challenges, including enhancing principals' competencies through holistic leadership training and promoting collaboration between principals, teachers, and school committees to develop both spiritual and academic capacities in a balanced manner.